1998
DOI: 10.1074/jbc.273.32.19955
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor ZBP-89 Regulates the Activity of the Ornithine Decarboxylase Promoter

Abstract: Appropriate cellular levels of polyamines are required for cell growth and differentiation. Ornithine decarboxylase is a key regulatory enzyme in the biosynthesis of polyamines, and precise regulation of the expression of this enzyme is required, according to cellular growth state. A variety of mitogens increase the level of ornithine decarboxylase activity, and, in most cases, this elevation is due to increased levels of mRNA. A GC box in the proximal promoter of the ornithine decarboxylase gene is required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 38 publications
4
79
0
3
Order By: Relevance
“…Results are an average from 4 -6 separate transfections of at least two different plasmid preparations, and error bars represent the S.E. tor, o-phenanthroline (47). We also observed this result for vimentin's repressor from HeLa NE (Fig.…”
Section: Figsupporting
confidence: 69%
See 2 more Smart Citations
“…Results are an average from 4 -6 separate transfections of at least two different plasmid preparations, and error bars represent the S.E. tor, o-phenanthroline (47). We also observed this result for vimentin's repressor from HeLa NE (Fig.…”
Section: Figsupporting
confidence: 69%
“…The first possibility was that only ZBP-89 can bind to the PS element and that Sp1 is held in this complex via proteinprotein interaction with ZBP-89. The second possibility was that, since the PS element is a GC-rich sequence, a binding site for Sp1 is located close to or overlapping ZBP's binding site as has been suggested for other ZBP-regulated genes (47). There-fore, Sp1 would be able to bind to the PS element along with, but independent from, ZBP-89.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZBP-99 had been isolated previously as binding a long CACC box from the gastrin gene promoter and shown to belong to a novel family of proteins defined by an array of four Kruppel-type zinc fingers (51). ZBP-99 was reported to inhibit transcription of the Ornithine decarboxylase gene similarly to its homologous factor ZBP-89/BFCOL1 (51,61). However, ZBP-89 has also been shown to activate transcription of the p21/waf1 gene through cooperation with histone acetyltransferase p300 in HT29 cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…During this study, several cDNAs that have identical sequences with mt␤ have been reported: BFCOL1 that binds to the proximal promoters of the type I collagen genes (27) and BERF-1, a 89-kDa protein that binds to a muscle-specific enhancer of the ␤-enolase gene (28). In addition, the rat and human homologue of the protein, ZBP-89, has been shown to bind to promoter regions of the gastrin gene (29) and the ornithine decarboxylase promoter (30). It has subsequently been reported that the same zinc finger protein also binds to the p21WAF1 gene (31), the matrix metalloproteinase-3 gene (32), the pT␣ gene (33), and the vimentin gene (34).…”
Section: Identification Of a Nuclear Protein Binding To The Lck Proximalmentioning
confidence: 99%